Diagnostic and treatment effects of sialendoscopy for patients with swelling of the parotid gland when sialoliths are undetected with computed tomography. Issue 4 (August 2018) - Kondo, Norio; Yoshihara, Toshio; Yamamura, Yukie; Kusama, Kaoru; Sakitani, Eri; Seo, Yukako; Tachikawa, Mayako; Kujirai, Keiko; Ono, Erika; Maeda, Yasuyo; Nojima, Tomohito; Tamiya, Akiko; et al.
Abstract: Between August 2009 and May 2016, 74 patients underwent sialoendoscopic surgery. 32 patients had parotid gland disease and 9 patients had intermittent swelling of the parotid gland and sialoliths were not detected with CT imaging. 4 patients were diagnosed with idiopathic Stensen's duct stenosis. Sialendoscopy directly confirmed Stensen's duct stenosis in 2 patients. However, the sialendoscope was unable to be inserted in the other 2 patients, who had stenosis of the orifice of the Stensen's duct. Balloon expansion of the duct was performed in these 2 patients and a steroid drug was injected into the duct in one patient. Complete remission was archived in one patient treated with sialendoscopy. Three patients had sialolithiasis. Microsialoliths and/or white floating matter was observed and removed using sialendoscopy. All patients experienced complete remission. In cases of Sjögren syndrome and recurrent parotitis, sialendoscopic surgery was performed, but the symptoms showed no improvement. For patients with microsialoliths, sialendoscopy may be most useful for diagnosis and treatment when the sialoliths are not detected with CT imaging. At present, sialendoscopic surgery have limitation in the treatment of Stensen's duct stenosis and may similarly have limitation in the treatment of Sjögren's syndrome and recurrent parotitis.